SISTEM INFORMASI GEOGRAFIS MENCARI RUTE LOKASI TRAVEL DI KOTA PALANGKA RAYA BERBASIS WEBSITE - Viktor Handrianus Pranatawijaya; Widiatry, Widiatry; Nova Noor Kamala Sari; Putu Bagus Adidyana Anugrah Putra (Universitas Palangka Raya, 2019)
Transport service or usually called travel1 is an inter-city transportation that many people use in Palangkaraya to travel among the cities. However, many people do not know the location of transport services in Palangkaraya and the informations obtained is still limited. Thus a system that provides computerized geographic information is needed. This study discusses the mapping of locations of transport services, location search, location data filters and the determination of the shortest path using the Dijkstra algorithm. For system development, it will apply the waterfall method. It is expected that the availability of a web-based system as a place to provide geographic information on the location of travel services is presented using the Google map API. In this study, the testing results for determining the shortest route on the public transport route can be determined by the Dijkstra algorithm. The transportation route is considered as a directed and weighted graph; the point represents a stop, and; side is as a vehicle lane. In the testing, firstly the user inputs the starting point on the map then looks for the destination on the destination search map, the system will display the initial shortest route output to the destination.